Discrimination Related to Labour Age Limitation in Indonesia: A Human Rights and Comparative Law Perspective - Prasetio, Dicky Eko; Masnun, Muh. Ali; Nugroho, Arinto; Ikram, Denial; Noviyanti, Noviyanti (Universitas Negeri Surabaya, 2024)
The existence of a maximum age limit for job applications in Indonesia presents societal challenges, as it has the potential to engender age-based discrimination, or ageism. This study aims to analyze the ratio decidendi of Constitutional Court Decision No. 35/PUU-XXII/2024, which addresses the maximum age limit for employment applications, while also examining human rights perspectives and legal comparisons related to maximum age limits in job vacancies in Indonesia. This research employs a normative legal methodology, utilizing case analysis, conceptual frameworks, legislative review, and comparative legal studies. The findings affirm that the ratio decidendi in Constitutional Court Decision No. 35/PUU-XXII/2024 concerning age limitations for certain job applications does not constitute discrimination, as age-based discrimination is not yet legislated in Indonesia. The maximum age limit in job vacancies can be classified as a form of ageism, which represents a type of discrimination based on age that should not be applied in the employment sector. Many countries, including Singapore, the Philippines, the United States, and Germany, have legislatively prohibited ageism and various forms of discrimination in job requirements and employment relationships. This study recommends that lawmakers revise the Labor Law to include ageism as a discriminatory practice. Keywords: Ageism, Human Rights, Employment, Comparative Law.